Personality in Kurdish Hayran with the Hayran Examples of Mustafa Kor Khoshawi (Raparin Journal of Humanities (RJH), 2026)
This research which is titled (Personality in Kurdish Hayran with the Hayran Examples of Mustafa Kor Khoshawi) is an attempt for analyzing personalities in Khoshawi’s hayrans and it sheds light on the relation between personality and hayran in Kurdish literature. It investigates personality aspect and the roles of those people that have been shown in the contents of those hayrans. The research gives importance to the relation between hayran and other fields of Kurdish literature like story and novel because they all have been gathered under the umbrella of Kurdish literature. Hayran can be regarded as the main column of constituting Kurdish folklore. The main goal of the research illustrates that hayran is not an ordinary conversation but rather it is a special literary structure that relates to personality, place and time. The method of analytical descriptive has been applied in this research. The result of this research has manifested that hayran and personality are the two faces of one coin and hayran cannot be separated from personality because the contents of hayrans are developed through personalities and they gain literary significance for themselves. After analyzing the texts of hayrans, we come to the conclusion that hayran is not only a literary art but rather a social instrument to deliver emotion and idea. The personalities in hayran have shown as semi facts of society which their aim consists of conveying expression and social message. this has been clearly shown in the hayrans of Mustafa Kor Khoshawi. In the end, the conclusion and abstract of the research have been demonstrated in English language and also the list of sources.